Karst and karst groundwater resources in the Mediterranean - Bakalowicz, Michel (Environmental earth sciences, 2015)
Karst landforms were first described and studied in Mediterranean regions, where these common landforms display their main hydrological characteristics. For this reason, Mediterranean karst is often considered to be the common reference. However, when we examine the general settings of Mediterranean karst and their groundwater resources more carefully, it becomes obvious that carbonate formations around the Mediterranean have been subject to various and complex conditions of development and functioning. This paper is an attempt to characterize the various types of carbonate karst aquifers present in the Mediterranean region according to the geological events that led to the development of different karst conditions. In terms of geological conditions, three major events caused the development of specific karst drainage structures that produced the various characteristics of Mediterranean carbonate aquifers: the Messinian Salinity Crisis (MSC) at the end of the Miocene, which caused rivers to incise deep valleys to reach the remaining sea, 1500–2500 m below the present sea level; cold periods during the Quaternary that caused weathering of the epikarst, even its destruction, which led to the development of a thick scree cover above an elevation of 1200–1500 m; and post-Miocene tectonics that generated extensional horst and graben structures, favored hydrothermalism and deep CO₂ flux, and caused continental sediments to fill in large basins in compressional environments. The main consequence of these complex geological conditions is the existence of large aquifers with successive karst structures developed at different depths and large storage capacities. When karstification occurred along the coasts, it may have caused carbonate aquifers to become connected to the sea, sometimes at great depths. Although it may be possible to provide an overall estimate of resources relatively easily from climatic and geological data, a groundwater storage assessment requires detailed knowledge of aquifer functioning and local geological evolution. Because of the complexity of karst development in Mediterranean regions, it is unrealistic to expect to manage them in a sustainable way without a thorough assessment of these karst aquifers.